Bread and beer: the production of the diet in Egyptian territory in ethnographic reports from Antiquity - Junqueira, Nathalia Monseff (Romanitas - Revista de Estudos Grecolatinos, 2025)
Ethnographic reports from Antiquity reveal some societies’ singularities listed in their pages. Political, military and everyday aspects are reported, imprinting mythological and rational explanations, which are characteristics of the thought developed in the ancient world. The aim of this article is to show the Egyptians’ diet, described in the narratives of the historians Herodotus (ca. 484-425 BC) and Diodorus Siculus (ca. 90-30 BC) as well as the geographer Strabo (ca. 64 BC - 23 BC). These travelers, who wrote in different historical contexts, were chosen for several reasons. The first one is due to their stay in Egypt for some years and because they shared a common culture, writing consistently in Greek. Such narratives shed light on the processes of food production in Egypt and possible changes, if any, from the Saitic to the Hellenistic periods. In addition, we will support our analysis with the material culture produced by the Egyptians in terms of food preparation, so that we can observe the way this society prepared bread and beer.
Keywords: Ancient Egypt; Food; Bread; Beer; Ethnographic reports